Optimalisasi Sumber Daya Perikanan dalam Mendukung Keselarasan Blue dan Green Economy di Tarakan: Optimization of Fishery Resources to Support the Harmony of Blue and Green Economy in Tarakan - Adiwena, Muh.; Kartina, Kartina; Santoso, Hadi; Nurhafida, Alisa; Muhajrah, Muhajrah; Jaya, Akbar (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Indonesia has great potential to sustainably utilize both marine and terrestrial resources. However, The Harapan Baru Cooperative Group still faces various challenges, such as limited knowledge of fish storage and the use of home gardens as cultivation areas for crops. This community service activity aims to address management and production issues to improve the economy of fishermen in the Harapan Baru Cooperative Group in Tarakan City, North Kalimantan, through the integration of blue economy and green economy concepts. The approaches used in this program include surveys, socialization, training, and evaluation. The identification results obtained during the survey revealed two main issues: the suboptimal income of partners from marine products and the minimal utilization of their yards for agriculture. In the training, partners were educated on various fish storage techniques and preservation methods, as well as the production of organic fertilizer from fish waste and botanical pesticides from Siam weed. The results of the activities showed an increase in understanding and skills among fishermen, especially regarding fish storage and micro farming, which can support local economic and food security. The evaluation results concluded that the average scores obtained by the participants indicated that the majority of partners have a good understanding, with a score of 80.2% for fish storage methods and 95% for the production of liquid organic fertilizer, compost, and botanical pesticides. These results reflect the success of the community service activities.